Importance of cancer among the Brazilian elderly population from 2000 to 2005 - Angelo Bezerra de Souza Fêde; Vanessa da Costa Miranda; Priscilla Guedes Pecoroni; Natália Moreno Perez Fraile; Maria Beatriz Brisola dos Santos; Suzana de França Ribeiro Gonzaga; Olinda do Carmo Luiz; Rachel Riechelmann; Auro del Giglio (Einstein (São Paulo), 2009)
Objective: To describe cancer hospital morbidity and mortality in the Brazilian elderly population according to the primary site of neoplasms per Brazilian region and their importance on Public Health System expenses. Methods: The data were obtained from the Ministry of Health records from 2000 to 2005. Rresults: From 2000 to 2005, there were 507,174 deaths due to neoplasms of the population older than 60 years old. The largest mortality rates were found in South and South-East regions. Among women, breast cancer was the most fatal neoplasm; among men, prostate cancer and trachea, bronchi and lung cancer. In situ neoplasms accounted for the highest average hospitalizations and the highest average expenses of the total amount paid for hospitalizations, while brain neoplasms accounted for the highest average amount spent per hospitalization. Cconclusions: The elderly population corresponds to the majority of deaths due to neoplasms in the Brazilian population and for most of the hospitalizations expenses due to oncologic causes and subsequent expenses of the public health system.